Analysis of Full-scale Load Tests on Bored Piles Socketed in Weathered Rock: A Case Study of the Subsoils of Phnom Penh Area - Ing, Khihok; Anantanasakul, Pongpipat (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 27, 2022)
Construction of high-rise buildings in the city of Phnom Penh has increased significantly in the past decade. The typical subsurface conditions of this urban area consist of a complex sequence of fluvial deposits of sandy and clayey soils underlain by sedimentary rock. Bored piles socketed in the rock layer have primarily been used as the foundation systems for such high-rise buildings. However, the current design knowledge of large-capacity bored piles in these particular ground conditions is rather limited. Due to the availability of the experimental results of full-scale static load test and high-strain dynamic tests on large-diameter bored piles, the present study was undertaken to gain better insight into the load transfer mechanisms as well as the settlement response of such deep foundations. A 2D axisymmetric finite element analysis was also performed to simulate the load-settlement relations obtained from the static load test. The experimental results indicated that skin friction significantly contributes to the pile mobilized capacities, to a degree much more than what previously thought by the local geotechnical community. The numerical predictions of the finite element model were observed to match the experimental load-settlement relationships fairly precisely. Parameter values of the soils and rocks that result in such realistic simulations of the pile response are presented herein.